Highly Conductive, Stretchable, and Transparent PEDOT:PSS Electrodes Fabricated with Triblock Copolymer Additives and Acid Treatment - Lee, Jin Ho; Jeong, Yu Ra; Lee, Geumbee; Jin, Sang Woo; Lee, Yong Hui; Hong, Soo Yeong; Park, Heun; Kim, Jung Wook; Lee, Sang-Soo; Ha, Jeong Sook (American Chemical Society, 2018)
Here, we report on a highly conductive, stretchable, and transparent electrode of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) fabricated via modification with triblock copolymer, poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (PEO20-PPO70-PEO20, Pluronic P123), and post-treatment with sulfuric acid. The fabricated electrode exhibits high transparency (89%), high electrical conductivity (similar to 1700 S/cm), and minimal change in resistance (similar to 4%) under repetitive stretch-release cycles at 40% tensile strain after stabilization. P123 acts as a secondary dopant and plasticizer, resulting in enhanced electrical conductivity and stretchability of PEDOT:PSS. Furthermore, after sulfuric acid post-treatment, P123 helps the electrode to maintain its stretchability. A successful demonstration of the stretchable interconnection was shown by stretching the P123-modified PEDOT:PSS electrodes, which were connected with light-emitting diodes (LEDs) in series. Finally, a stretchable and transparent touch sensor consisting of our fabricated electrodes and an LED array and stretchable semitransparent supercapacitor were presented, suggesting a great potential of our electrodes in the application to various deformable devices.
Keywords: ORGANIC SOLAR-CELLS; ORDERED MESOPOROUS CARBONS; ELECTRICAL-CONDUCTIVITY; PSS FILMS; PEDOT/PSS; MORPHOLOGY; EFFICIENCY